CITY, GOVERNMENT, AND INHABITANT: SOCIAL CRITICISM IN THE SHORT STORY NENEK PENUNGGU KERETA BY ADE UBAIDIL - Sugiarto, Septian Rifki (Jurnal Ilmu Bahasa, Sastra dan Pengajarannya, 2024)
Literary works are a medium that is often used to carry out social criticism. For example, criticism of the state of the city, the badness of the government, or the behavior of city residents. The short story “Nenek Penunggu Kereta” by Ade Ubaidil is one of the literary works that contains criticism of these three things. Therefore, this study discusses the portrait of the city, government, and city residents in the short story to see the social criticism conveyed by the author. In order to answer this problem, this study uses a sociology of literature approach and representation theory. The data collection technique used in this study was recording, while the data analysis technique used the interpretation analysis technique. The results of this study indicate that the depiction of a gloomy and chaotic city in the short story is a form of social criticism of government policies that have failed to manage and improve the quality of life. Instead of improving the situation, the government actually seems to worsen the situation and continues to make false promises. In addition, there is also criticism of the behavior of inhabitants who are willing to accept rewards ahead of the election. The author wants to emphasize that everyone must be more sensitive to government policies and choose quality leaders.